Disposable array sensor strip for quantification of sinensetin in Orthosiphon stamineus Benth samples - Mohd Noor, Ahmad; Yap Mee Sim, Maxsim; Chang Chew, Cheen; A. K. M., Shafiqul Islam; Zhari, Ismail; Misni, Surif; Ali Yeon, Md Shakaff; Larisa, Lvova (Springer-Verlag, 2009)
Link to publisher's homepage at http://www.springerlink.com/content/b63173154165m401/